Towards Proper Sizing Experiments: Analysis of the Impact of Measurement Conditions and Sample Preparation on the Size Estimation of the Nanodroplets and Nanoparticles - Nikolić, Ines; Randjelović, Danijela; Savić, Snežana (Archives of Pharmacy, 2022)
Physicochemical properties of many active ingredients jeopardize their pharmacological activity. To overcome identified obstacles, nanosystems as carriers for delivery of actives have been recognized as promising tools, with highly posted expectations. The nanotechnology-based approach in drug formulation is much more than just another step in size miniaturization. Given the complexity of nanosystems, challenges encountered in their characterization, and evident lack of testing protocols, relevant European research/regulatory bodies have issued guidelines, summarizing important parameters for nanosystem characterization. Size/size distribution (per se and in biorelevant environment) are essentially important, representing critical quality attributes. The aim was to show how significantly different results could be obtained under different measurement conditions/sample preparation methods, offering optimal protocol for size estimation applying dynamic light scattering (DLS), with complementary analysis through atomic force microscopy. Hydrophilic nanoemulsion and aqueous dispersion of polymeric nanoparticles were used as test samples. Ultrapurified water, phosphate buffer saline (PBS, pH 7.4) and biorelevant medium with serum proteins were used for dilution. Measurements were performed applying batch-mode DLS (ZetasizerNano), and AutoProbe CP-Research microscope. Significant differences in obtained nanodroplet/nanoparticle size ​​were observed depending on the type of medium and dilution level. Protein corona formation could not be confirmed with certainty. Preference was given to PBS as dispersant. The optimal level of dilution for nanoparticles was 1:10 (Z-ave=59.16±0.46nm), and for nanoemulsion 1:100 (Z-ave=73.5±0.75nm). For proper interpretation, it is necessary that the DLS measurement report, in addition to the Z-ave and the polydispersity index, contains at least the data on the attenuation and correlation function intercept.